Powder and patch - Heyer, Georgette (Naperville, Ill. : Sourcebooks Casablanca, 2010)
Wanting to win over the woman he loves, Philip leaves for Paris-- to learn to be a gentleman.
Keywords: Mate selection; British -- France -- Paris; British -- Paris (France); Love stories; Regency fiction; Fiction